The Human in the Context of a Posthuman World. - Szilagyi, Nicolae Andrei (Caietele Echinox, 2018)
The progress that humanity has made so far in its development in so many fields is certainly something commendable. However, as with all complex notions, there is another side to it as well. This essay sets out to analyze several of the recent breakthroughs in the field of robotics and draws a few parallels between the promise of a bright future and a handful of rather different scenarios, all highlighting one fundamental figure and the role it has played during this entire process. Thus, the figure of the human is emphasized as the key factor even though the context seems to require its presence evermore rarely, perhaps up to a point where this flawed figure will finally be replaced by the flawless machine it has created.